A study on illustration for traditional Malay poem book layout design / Arisya Azlan - Azlan, Arisya (2019)
The role that illustrations can play in books, newspaper and magazines are a huge impact to the society. Illustrations have been shown to help in demonstrating pictures and the attractiveness of illustration helps to attract people’s attention to it. Illustrations are also commonly found in some books for adults as well. Illustrating poetry is an excellent way to learn about the specie c literary devices – such as imagery – used in creative writing. Poetry illustrations allow you to create a personal interpretation of the work by exploring the dierent layers of rhythm, character, cadence, imagery and other poetic techniques. Generally, speaking, the purpose is on how to conserve the Malay traditional poetry as a form of illustration book. As for Malay poems, are the principal forms of traditional Malay poetry that take the form of pantun, syair and gurindam. A gurindam is a two-line piece, with a single rhyme, each gurindam is complete in terms of idea or theme presented. It usually contains advice or teaching, presented through elegant similes or metaphors. It is mostly from the Malay’s observations, re action of their cultural environment and practical experiences. The advice or teaching in the Malay poem must be passed on in order to conserve them especially amongst the younger Malay generation. By creating an illustration book, it will be a transmitter of Malay literature and culture knowledge from generation to generation in the society so it won’t just fade away. It is also a fact that the human brain perceives visual information fully, quickly and holds it longer in your memory than texts does. Gurindam Jiwa is a classic Malay song that is still popular until today among the senior citizens and not so popular among the youngsters. Therefore, by creating an illustration poem book can attract more people of all age towards the visual and at the same time, appreciating the beauty and the soul of the poems that is a part of the Malay culture.